2020
DOI: 10.1108/jcm-05-2018-2681
|View full text |Cite
|
Sign up to set email alerts
|

Cultural norms and the marketplace: favor economies in the Arab world

Abstract: Purpose Recent scholarship has highlighted the complexity of buyer-seller relationships in emerging markets and called for a better understanding of the cultural norms shaping such relationships. This paper aims to draw on social capital theory to explore the role of networks and relational norms, such as wasta, in Arab culture on consumer relational behaviors. The Arab market constitutes a significant economy and social networks and relational norms are of significant value in Arab culture. Design/methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Consumers seem to be making more ethical and environmentally friendly purchases, but they also demonstrate a high degree of materialism: this consumption is quite conspicuous, and consumers buy such products even though their prices are far above normal. Moreover, the tendency of ethnocentrism drives group consciousness and feelings of cooperative energy and empathy to support consumers' social groups [33]. This was evident when the COVID-19 pandemic hit Indonesia: calls were made in the media, including on social media, for consumers to buy at small stalls in their communities to help those businesses survive the economic recession.…”
Section: E Categorical Cognition Theorymentioning
confidence: 99%
“…Consumers seem to be making more ethical and environmentally friendly purchases, but they also demonstrate a high degree of materialism: this consumption is quite conspicuous, and consumers buy such products even though their prices are far above normal. Moreover, the tendency of ethnocentrism drives group consciousness and feelings of cooperative energy and empathy to support consumers' social groups [33]. This was evident when the COVID-19 pandemic hit Indonesia: calls were made in the media, including on social media, for consumers to buy at small stalls in their communities to help those businesses survive the economic recession.…”
Section: E Categorical Cognition Theorymentioning
confidence: 99%
“…Previous research has already demonstrated that service failure and recovery influences consumers’ perceptions of fairness (Gelbrich and Roschk, 2011), their emotional responses (Valentini et al , 2020) and their repurchase (Kanuri and Andrews, 2019), forgiveness and retaliation intentions (Atav et al , 2021), satisfaction and word-of-mouth (WOM) (Bonifield and Cole, 2008; Hoegreve et al , 2017). Cultural values have also been the focus of extensive research, which investigated their impact on consumer perception and behavior (El Jurdi and Houjeir, 2020; Nath, 2018; Moro et al , 2020) and their relation to service failure and recovery (Matos et al , 2011; Schoefer et al , 2019; Sengupta, 2020; Zhang et al , 2021).…”
Section: Introductionmentioning
confidence: 99%